COMPARATIVE ANALYSIS OF DIFFERENT WAYS OF LASER TREATMENT OF SCARS OF THE FACE SKIN - Нагірний, Я.П. (World of Medicine and Biology, 2015)
Abnormal scarring of the skin that occur after suffering burns, injuries, and after planned operations, not only create discomfort but also distorting the person often cause serious functional impairment up to disability, leading to the development of neuropsychiatric disorders that impairs quality of life and limit performance. Currently, there is no single approach to the scar treatment. When comparing two treatments for hypertrophic scars we found improvement in all patients in the group where treatment was carried out using a laser perforation surface scar. The evolution of the Vancouver scale in this group correlated with high clinical efficacy. In our opinion, these results can be explained by low invasiveness methods, rapid healing time, which leads to a controlled restructuring of hypertrophic scar.
Keywords: hypertrophic scars; laser dermabrasion; clinical efficiency